2018
DOI: 10.1186/s12884-018-2120-7
|View full text |Cite
|
Sign up to set email alerts
|

Rates of HBV, HCV, HDV and HIV type 1 among pregnant women and HIV type 1 drug resistance-associated mutations in breastfeeding women on antiretroviral therapy

Abstract: BackgroundHBV, HCV, HDV and HIV are blood borne and can be transmitted from mother-to-child. Reports of HBV infection rates show up to 11.9% in Cameroon while for HCV, the rate is less than 2%. More so, as pregnant women get enrolled in the HIV PMTCT Programme and stay in the care continuum, selection of HIV-1 drug resistant strains is evident. We sought to determine the seroprevalence of HBV, HCV, HDV and HIV among pregnant women, assess their knowledge, attitudes and practices on transmission and prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
6
10
2
Order By: Relevance
“…This study showed high rates of NNRTI mutations, with K103N being the most prevalent, followed by NRTI mutations, with M184V/I being the most prevalent, which is in accordance with a prior study at our centre [4]. Similarly, in studies of PPLH in Cameroon and the Bahamas, rates of antiretroviral resistance were highest against NNRTI (EFV and NVP) and NRTI [lamivudine (3TC) and zidovudine (ZDV)] [10,11]. In the WHO report [5], the overall prevalence of resistance among ART-naïve women living with HIV was 14.2% to NNRTI, 7.7% to NRTIs, 0.4% to PIs and 0.3% to INSTIs; the overall pretreatment resistance to second-generation NNRTIs was in the range 0.5-13.2% for doravirine (DOR), 1-10.3% for etravirine (ETR) and 2.4-18.7% for rilpivirine (RPV) [5].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study showed high rates of NNRTI mutations, with K103N being the most prevalent, followed by NRTI mutations, with M184V/I being the most prevalent, which is in accordance with a prior study at our centre [4]. Similarly, in studies of PPLH in Cameroon and the Bahamas, rates of antiretroviral resistance were highest against NNRTI (EFV and NVP) and NRTI [lamivudine (3TC) and zidovudine (ZDV)] [10,11]. In the WHO report [5], the overall prevalence of resistance among ART-naïve women living with HIV was 14.2% to NNRTI, 7.7% to NRTIs, 0.4% to PIs and 0.3% to INSTIs; the overall pretreatment resistance to second-generation NNRTIs was in the range 0.5-13.2% for doravirine (DOR), 1-10.3% for etravirine (ETR) and 2.4-18.7% for rilpivirine (RPV) [5].…”
Section: Discussionsupporting
confidence: 91%
“…According to the 2022 International Antiviral Society (IAS)‐USA Drug Resistance Mutation Update, the magnitude of the reduction in susceptibility varies considerably, with those defined as major mutations most closely related to premature treatment failure and associated with significant reductions in susceptibility [8]. Our finding of high prevalence of K103N is similar to other studies [5, 10–12]. Among the participants in this study with E138A/G/K/Q mutations, all of them had subtype B.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In Federal Ministry of Health (FMOH) and World Health Organization report, Nigeria has a high burden of hepatitis C at a prevalence rate of 2.0%, 17 hence women that received antenatal health care in the AMURT supported rural health facilities in Ebonyi state have a high HCV prevalence rate. This is higher than the findings of other studies in Nigeria which were: 2.6% in Enugu, 35 0.8% in Edo State, 37 0.5% in Niger delta, 45 1.1% in Okada, Edo state, 46 0.8% among Cameroonian women, 56 and 1.8% in Southern Ethiopia. 54 The result is lower than the findings outside Nigeria in places like Western Ethiopia where HCV prevalence of 8.1%.…”
Section: Discussioncontrasting
confidence: 67%
“…HBV and HDV are common viruses for coinfection in people living with HIV, as all 3 share the same route of infection [ 14 , 35 ]. Studies have shown that HIV coinfection with HBV and HDV is widespread in various regions of the world, but the coinfection rate varies among countries and regions [ 36 ]. HIV coinfection with HBV or HDV can cause more serious damage to the body than a single infection, and the harm of triple infection is even more serious.…”
Section: Discussionmentioning
confidence: 99%